Acute liver failure following decompression of intussusception in an infant - A case report - Maria Turcanu; Yaw Asamoa-Bonsu (Journal of Pediatric Critical Care)
Intussusception is a common pediatric surgical emergency, but its complications can be severe. We present the case of an 8-month-old boy with hematochezia and projectile vomiting, diagnosed with intussusception requiring emergent laparotomy after failed contrast enemas. Postoperatively, he developed worsening abdominal distension, persistent fevers, and transaminitis (aspartate transferase – 6000, alanine transferase – 2000, and INR – 4), progressing to acute liver failure (ALF). Imaging revealed ascites, hepatomegaly, and pericholecystic fluid. Despite broad-spectrum antibiotics and extensive workup for infectious, autoimmune, and hematologic causes, his liver dysfunction worsened. Surgical exploration on hospital day 3 revealed a necrotic cecum with a contained perforation, necessitating a right hemicolectomy. Postoperatively, inflammatory markers, transaminases, and synthetic liver function improved. This case highlights severe systemic inflammatory response syndrome (SIRS) following intussusception reduction, which led to ALF through ischemic and inflammatory mechanisms. Early recognition and aggressive management of postoperative SIRS are critical to preventing multi-organ dysfunction, including ALF.